The fungicide mancozeb affects soil invertebrates in two subtropical Brazilian soils - Camargo Carniel L.S.* (2019)
© 2019Mancozeb is a dithiocarbamate non-systemic fungicide widely used to control fungal diseases of plants, commonly applied in apple orchards in Brazil. Instead of its common use, there are no reports about the risk to non-target organisms in Brazilian soils. We studied the risk of Mancozeb (in the commercial formulation Dithane® NT) for standard invertebrate species (Folsomia candida, Eisenia andrei and Enchytraeus crypticus) in two subtropical Brazilian soils, Oxisol and Ultisol, which are representative of apple production areas in Brazil. Reproduction and survival tests were carried out following ISO guidelines. Results showed that Mancozeb in Oxisol reduced the survival and reproduction of collembolans (LC50 54.43 and EC50 2.72 mg a.i. kg-1) and enchytraeids (LC50 6.97 and EC50 3.56 mg a.i. kg-1), in lowest values than those observed in Ultisol (F. candida LC50 > 1000 and EC50 > 100 mg a.i. kg-1; E. crypticus LC50 280.21 and EC50 29.67). Effects to E. andrei were similar in both soils and indicated a lower sensitivity of this species to Mancozeb. The species F. candida and E. crypticus were more sensitive than E. andrei. These results reinforce the need to include other soil organisms besides earthworms, using chronical endpoints and considering different types of soils, to better predict the risk of pesticides for subtropical soils.